Air–water interfacial synthesis of metal–organic framework hollow fiber membranes for water purification. Issue 7 (24th April 2020) - Wu, Wufeng; Jia, Miaomiao; Su, Jingyi; Li, Zhanjun; Li, Wanbin
Abstract: In this study, we report a novel air–water interfacial self‐crystallization (AWISC) method for scalable depositing continuous metal–organic framework (MOF) layers on modification‐free polyvinylidene fluoride (PVDF) hollow fibers. Through importing MOF precursors into porous hollow fiber substrates with outer diameters of 1.2 mm and evaporating aqueous solutions under mild conditions, the metal ions and linkers close to solution surface can be concentrated firstly, thus the crystallization of MOFs will preferentially occur at interface of air and liquid precursors. The formed crystals can block off the pores of substrates to form defect‐free MOF membranes. The prepared ZIF‐8 membranes exhibit superior performance in molecular separation, with high rejections of 94.1 ∼ 99.5% for small molecules (molecular weight: 320 ∼ 800 Da) and large permeance up to 50 L m −2 h −1 bar −1 . Moreover, by combining AWISC and microfluidic processing, the high‐performance ZIF‐8 hollow fiber membranes with long length of 30 cm can be easily fabricated in scalability.